'No strings attached?': How attribution of disinterested support affects employee retention. (27th March 2012) - Mignonac, Karim; Richebé, Nathalie
<x xml:space="preserve">Abstract</x> Appearance of disinterestedness is a social norm that has long been recognised by social scientists as essential to the development of social exchange relationships. Despite the predominance of social exchange theory within the field of management, management scholars have so far largely overlooked the role of this norm in their models. This study aims to fill this gap by investigating how employees' attribution of disinterested organisational support (i.e. support perceived by employees as not resulting from an underlying calculation) is related to employee retention. The hypotheses were tested in a longitudinal study of 151 management‐level employees. Results showed that perceptions of disinterested support decrease employee voluntary turnover through enhancing perceptions of organisational support and organisational commitment, and lessening turnover intention.